ENHANCE CONTROLLING SMART CHARGING TIME - Indra Gunawan Yusuf Siregar; Siti Anisah; Muhammad Rizki Syahputra (Jurnal Scientia, 2023)
In this research discusses the storage of electrical energy into the battery itself must be managed in such a way that the process of charging and discharging the battery can take place properly, without causing the load to go out due to running out of battery power. designed a tool to compare the charging time of several batteries with charging using a solar tracker or not using a solar tracker to find out which battery is more efficient in its use. This research uses lead acid batteries, lithium ion batteries, and nickel-cadnium batteries. From the results of this study it is known that lead acid batteries have a charging time of 3 hours 30 minutes without using solar trackers and 3 hours 15 minutes using solar trackers with an efficiency of 7.14%, lithium ion batteries have a charging time of 3 hours 30 minutes without using solar trackers and 3 hours using solar trackers with an efficiency of 14.29%, while Nickel-Cadnium batteries have a charging time of 4 hours 30 minutes without using solar trackers and 4 hours 45 using solar trackers with an efficiency of 11.11%. Then it was found that lithium ion batteries have the fastest charging time of the three batteries used. The system is controlled by an Arduino UNO microcontroller, input in the form of 3 voltage sensors, 6 relays as actuators. relays as actuators, LCD as battery status displayer, and buzzer as warning sound actuator. sensor voltage sensor reads the voltage value on all installed batteries, then Arduino UNO will process the battery with a value above the setpoint. which has a value above the setpoint will be connected to the load through the load relay, while the battery whose voltage is below the setpoint value will be connected to the load. below the setpoint value will be connected to the charging system through the charging relay. In this study given The design of the battery monitoring and management system with the Arduino UNO microcontroller-based switching method has been successfully realized.